Roadside verges support greater ecosystem functions than adjacent agricultural land in a grassy woodland. (15th April 2022) - Ding, Jingyi; Eldridge, David J.
Abstract: Vegetation clearance is the major land use change in agricultural landscape, where woody species are removed to support agricultural production. Native woody species are now largely restricted to the thin strips along the road (roadside verges). Despite the importance of roadside verges as refugia for native species, their impacts on ecological functions and the driving factors have been little explored over extensive areas, limiting our capacity to argue for the retention and improvement of these 'off-reserve' habitats within agroecosystems. We compared the magnitude of ecological functions between paired roadside verges and adjacent agricultural land at 111 sites along a vegetation condition gradient in eastern Australia to examine the ecological importance of roadside verges and the potential regulators. Eighty-six percent of our 21 ecological attributes differed between roadsides and adjacent agricultural land, with roadside verges supporting greater carbon stocks, vegetation coverage, plant diversity, habitat complexity and tree recruitment, and were subject to less modification and erosion. These ecological effects strengthened with increasing roadside verge width, particularly for plant cover and diversity, the proportion of native plant species and habitat complexity. Management practices were major regulators of roadside functions, with roadside verge width and site modification negatively associated with tree recruitment and the soil organic carbon pool. Site modification and roadside verge width also indirectly reduced the soil organic carbon pool by either suppressing tree diversity or promoting the proportion of native plant species. Our study provides empirical evidence of the ecological importance of roadside verges in maintaining ecosystem functions and the sustainability of native plant communities in peri-agricultural landscapes. Our study also demonstrates the negative effects of site modification on tree recruitment and soil organic carbon pools, highlighting the importance of mitigating management activities (e.g., tree removal, fire, grazing) in the conservation of roadside verges. Highlights: Most eucalypt species (77%) showed evidence of recruitment in roadsides. 18 ecological attributes are significantly different between roadsides and paddocks. The magnitude of ecological effects increased with increasing roadside width. Tree recruitment and soil carbon pool are negatively affected by site modification.